Endodontic micro-resurgery and guided tissue regeneration of a periapical cyst associated to recurrent root perforation: a case report - Cordova-Malca, Fernando; Coaguila-Llerena, Hernan [UNESP]; Garre-Arnillas, Lucia; Rayo-Iparraguirre, Jorge; Faria, Gisele [UNESP] (Korean Acad Conservative Dentistry, 2022)
Although the success rates of microsurgery and micro-resurgery are very high, the influence of a recurrent perforation combined with radicular cyst remains unclear. A 21-year-old white female patient had a history of root perforation in a previously treated right maxillary lateral incisor. Analysis using cone-beam computed tomography (CBCT) revealed an extensive and well-defined periapical radiolucency, involving the buccal and palatal bone plate. The perforation was sealed with bioceramic material (Biodentine) in the pre-surgical phase. In the surgical phase, guided tissue regeneration (GTR) was performed by combining xenograft (lyophilized bovine bone) and autologous platelet-rich fibrin applied to the bone defect. The root-end preparation was done using an ultrasonic tip. The retrograde filling was performed using a bioceramic material (Biodentine). Histopathological analysis confirmed a radicular cyst. The patient returned to her referring practitioner to continue the restorative procedures. CBCT analysis after 1-year recall revealed another perforation in the same place as the first intervention, ultimately treated by micro-resurgery using the same protocol with GTR, and a bioceramic material (MTA Angelus). The 2-year recall showed healing and bone neoformation. In conclusion, endodontic micro-resurgery with GTR showed long-term favorable results when a radicular cyst and a recurrent perforation compromised the success.
Keywords: Apicoectomy; Guided tissue regeneration; Platelet-rich fibrin; Retreatment; Radicular cyst